Bedload hysteresis in a glacier‐fed mountain river. Issue 7 (8th April 2014) - Mao, Luca; Dell'Agnese, Andrea; Huincache, Carolina; Penna, Daniele; Engel, Michal; Niedrist, Georg; Comiti, Francesco
ABSTRACT Sediment transport during flood events often reveals hysteretic patterns because flow discharge can peak before (counterclockwise hysteresis) or after (clockwise hysteresis) the peak of bedload. Hysteresis in sediment transport has been used in the literature to infer the degree of sediment availability. Counterclockwise and clockwise hysteresis have been in fact interpreted as limited and unlimited sediment supply conditions, respectively. Hysteresis has been mainly explored for the case of suspended sediment transport, but it was rarely reported for bedload transport in mountain streams. This work focuses on the temporal variability of bedload transport in an alpine catchment (Saldur basin, 18.6 km2, Italian Alps) where bedload transport was monitored by means of an acoustic pipe sensor which detects the acoustic vibrations induced by particles hitting a 0.5m‐long steel pipe. Runoff dynamics are dominated by snowmelt in late spring/early summer, mostly by glacier melt in late summer/early autumn, and by a combination of the snow and glacier melt in mid‐summer. The results indicate that hysteretic patterns during daily discharge fluctuations are predominantly clockwise during the snowmelt period, likely due to the ready availability of unpacked sediments within the channel or through bank erosion in the lower part of the basin. On the contrary, counterclockwise hysteresis tend to be more frequent during late glacier melting period, possibly due to the time lag needed for sediment provided by the glacial and peri‐glacial area to be transported to the monitoring section. However, intense rainfall events occurring during the glacier melt period generated predominantly clockwise hysteresis, thus indicating the activation of different sediment sources. These results indicate that runoff generation processes play a crucial role on sediment supply and temporal availability in mountain streams. Copyright © 2014 John Wiley & Sons, Ltd.